Hypersensitivity Reactions to Ophthalmic Products - Ventura, M. T.; Viola, M.; Gaeta, F.; Di Leo, E.; Buquicchio, R.; Romano, A. (Current Pharmaceutical Design, 2006)
Adverse reactions after administration of ophthalmic products have frequently been observed. These reactions can be provoked by both active principles and excipients. Different pathogenic mechanisms have been suggested for such reactions, including immunologic ones. Basophils and mast cells participate in IgE-mediated reactions through the release of mediators like histamine and tryptase, whereas a T-cell-mediated pathogenic mechanism is involved in most delayed reactions, particularly conjunctival ones and eyelid dermatitis. Prick tests and immediate-reading intradermal tests are carried out to diagnose immediate hypersensitivity reactions, while patch tests are usually performed to evaluate delayed reactions. Other diagnostic tests, such as serum-specific IgE assays in immediate reactions, as well as delayed-reading intradermal tests and/or lymphocyte transformation tests in delayed ones, are rarely performed. In this review, particular attention is addressed to the clinical and practical aspects of both cell-mediated and IgE-mediated hypersensitivity reactions to ophthalmic products.
Keywords: ophthalmic products